Switching of hydrophilic to ultra hydrophilic properties of flower-like gold nanostructures - Dhumale, Vinayak A.; Shah, Preeti V.; Mulla, Imtiaz S.; Sharma, R. B. (Applied Surface Science, 2010)
Flower-like morphologies of gold nanostructures were obtained via chemical method by controlling molar concentration ratio of reducing agent and precursor. Chloroauric acid was used as a metal precursor while tri-sodium citrate as the reducing agent. These flower-like structures were characterized by UV-vis spectroscopy, Scanning Electron Microscopy (SEM) and X-ray Diffraction (XRD) techniques. The basic crystallite size calculated via XRD measurement was found to be similar to 10 nm and remain unaffected by the different concentration ratios. The coating of these structures was made over clean glass substrate and analyzed for wettability by measuring their water contact angles. Our analysis indicates that the coatings of hierarchical flower-like structures of gold are able to provide ultra hydrophilic properties to glass substrate. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Gold flower-like nanostructures; Ultra hydrophilic; Wettability

Synthesis of cube-shaped gold nanostructures by electron irradiation - Dhumale, Vinayak A.; Gangwar, Rajesh K.; Shah, Preeti V.; Bhoraskar, Vasant N.; Mulla, Imtiaz S.; Sharma, Rishi B. (Materials Letters, 2011)
The needle-like gold nanostructures were synthesized by using chloroauric acid (HAuCl(4)) as a metal precursor and sodium borohydride (NaBH(4)) as the reducing agent. These needle-like nanostructures of gold were irradiated with high energy electrons (E-6 MeV, phi similar to 10(12) e cm(-2) s(-1)). The pre- and post-irradiated gold nanostructures were characterized by Scanning Electron Microscopy (SEM), UV-vis spectroscopy, X-ray Diffraction (XRD) and contact angle measurement (GBX-Model Digidrop) techniques. The results of the SEM revealed that after electron irradiation, the needle-like gold structures got fragmented into identical cube-shaped gold nanostructures, though of different sizes. The XRD analysis indicated that the average crystallite size of the gold nanostructures remained unchanged even after irradiation with high energy electrons. A glass surface showed hydrophilic behavior when coated with needle-like nanostructures and became ultra hydrophilic when coated with cube-shaped gold nanostructures. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Gold nanostructures; High energy electron irradiation; Nanostructured materials; Radiation damage; Surfaces; Ultra hydrophilic surfaces